Elastin Structure, Synthesis, Regulatory Mechanism and Relationship With Cardiovascular Diseases - Wang, Keke; Meng, Xiangguang; Guo, Zhikun (Frontiers in Cell and Developmental Biology, 2021)
As the primary component of elastic fibers, elastin plays an important role in maintaining the elasticity and tensile ability of cardiovascular, pulmonary and many other tissues and organs. Studies have shown that elastin expression is regulated by a variety of molecules that have positive and negative regulatory effects. However, the specific mechanism is unclear. Moreover, elastin is reportedly involved in the development and progression of many cardiovascular diseases through changes in its expression and structural modifications once deposited in the extracellular matrix. This review article summarizes the role of elastin in myocardial ischemia-reperfusion, atherosclerosis, and atrial fibrillation, with emphasis on the potential molecular regulatory mechanisms.